Konsep Dasar Karakter Mendidik dalam Perspektif Hadis - Ayi Teiri Nurtiani; Cut Fazlil Hanun (IAIN TERNATE, 2022)
Parents are the first educators in children's lives from an early age, as well as the main role models in the formation of their Islamic character. In educating, parents are also obliged to imitate the Prophet Muhammad SAW as a figure of uswatun hasanah and a role model for parents in educating their children, so that children have Akhlakul karimah and become insan kamil in upholding the commands of Allah SWT. Efforts to educate children will also run effectively and intact if it involves three institutions, namely the family (informal education), schools (formal education) and the community (non-formal education). Educators, both parents and teachers, are required to have the following educational characteristics: 1) A sense of responsibility; 2) Calm down; 3) Soft nature; and 4) the nature of compassion; and 5) Patience, so that all children's potentials develop optimally